Linear and branched acetal polymers from castor oil via acetal metathesis polymerization. (November 2018) - Moreno, Adrian; Lligadas, Gerard; Ronda, Juan Carlos; Galià, Marina; Cádiz, Virginia
Graphical abstract: Highlights: Synthetic protocols are developed to prepare new diols from heptanal. Linear and branched polyacetals are obtained by acetal metathesis polymerization. Similar acidic degradation patterns are obtained regardless of polyacetal structure. Abstract: Synthetic protocols to prepare new diols were developed to revalorize heptanal and 10-undecenoic acid castor oil derivatives. The Acetal Metathesis Polymerization of these diols yielded linear and branched renewable polyacetals and copolyacetals with number average molecular weights in the range 14, 000–27, 000 g mol −1 . Thermally robust semicrystalline or amorphous materials were obtained. Polyacetals were hydrolytically degradable down to parent diols under slightly acidic media and no significant differences on the degradation pattern were observed among them.